Zafirlukast ameliorates Docetaxel-induced activation of NOD-like receptor protein 3 (NLRP3) inflammasome, mediated by sirtuin1 (SIRT1) in hepatocytes. Issue 2 (20th December 2021) - Guo, Ziyi; Zeng, Xunjin; Zheng, Yu
ABSTRACT: Docetaxel-associated liver injury has become a serious public health problem, resulting in therapy discontinuation, liver failure, and death. Zafirlukast is a typical leukotriene receptor antagonist used for prophylaxis and chronic treatment of asthma. In this study, we investigate whether treatment with Zafirlukast could alleviate Docetaxel-induced cytotoxicity in hepatocytes. Our results indicate that Zafirlukast mitigated Docetaxel-induced toxicity in LO-2 hepatocytes. Firstly, Zafirlukast reduced the production of 8-hydroxy-2p-deoxyguanosine (8-OHdG) and increased the levels of reduced glutathione (GSH) against Docetaxel. Secondly, Zafirlukast elevated the levels of mitochondrial membrane potential (ΔΨm) and adenosine triphosphate (ATP). Thirdly, Zafirlukast prevented Docetaxel-induced release of lactate dehydrogenase (LDH) and increased cell viability of LO-2 hepatocytes against Docetaxel. We also found that Zafirlukast ameliorated Docetaxel-induced apoptosis by reducing Caspase-3 and Caspase-9 activity. Mechanistically, our results demonstrate that Zafirlukast inhibited the activation of NOD-like receptor protein 3 (NLRP3), mediated by SIRT1. Based on these findings, we conclude that the administration of Zafirlukast might have a protective effect against Docetaxel-induced cytotoxicity in hepatocytes.